The Role of Parenting and Peer Pressure in the Development of Juvenile Delinquent Behaviour among Higher Secondary School Children in Punjab, Pakistan: A Proposed Framework - Ashraf, Muhammad Umair; Ahmad, Abd Halim; Talib, Azlizan (IJICC, 2019)
This study proposes a research framework about the role of parenting and peer pressure, and their effects on juvenile delinquent behaviour among secondary school children in Punjab, Pakistan. This research framework has been developed after an extensive review of empirical literature. Previous studies were scarce in regard to those that attempted to examine the combined effect of parental behaviour, family structure, family socioeconomic status, and peer pressure on juvenile delinquent behaviour, especially in a Pakistani cultural context. The existing literature failed to find consistency in the relationship between parenting, peer pressure and juvenile delinquent behaviour, particularly in the context of the present research. The present study adds to existing literature by identifying factors which reduce the chance of juvenile delinquent behaviour. This research also delivers valued information for parents, policymakers, teachers, psychologists, sociologists, criminologists, child protection departments, and governmental institutions